Association Between Age of Beginning Primary School and Attention Deficit Hyperactivity Disorder - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Objective: In April 2012, the Turkish national education system was modified, and the compulsory school age of entry (first grade) was redefined as a minimum of 60 months and a maximum of 66 months (replacing the former minimum criterion of 72 months). In this study, we hypothesized that students starting school before 72 months (the previous age standard for the first grade) may experience (1) a greater number of symptoms of attention deficit hyperactivity disorder (ADHD) and (2) lower functioning in social, behavioral, and academic domains. Method: We performed a cross-sectional community-based study in the first and second grades of all primary schools (4356 students) located in the Kadkoy county of Istanbul, Turkey. Teachers completed Swanson, Nolan, and Pelham version IV and Conners' Teacher's report forms for symptoms of ADHD, the Perceived Competence Scale for functioning, and a sociodemographic questionnaire. Results: Among first graders, the group that began primary school before the age of 72 months had a higher ADHD prevalence than both of the groups that began primary school between the ages of 72 to 77 months and 78 to 83 months (p < .001 for both groups). ADHD symptoms diminished and academic, social, and behavioral functioning improved with age for the first and second grade students. Conclusion: The probability of displaying ADHD symptoms (and caseness) is greater among the earlier beginners, whereas the conventional classmates exhibited better academic, social, and behavioral functioning.
Keywords: attention-deficit/hyperactivity disorder; age; children; prevelance; primary school; CHILD MENTAL-HEALTH; DEFICIT/HYPERACTIVITY DISORDER; RELATIVE AGE; RISK-FACTORS; ADHD; PREVALENCE; INTERVENTION; METAANALYSIS; DIAGNOSIS; SYMPTOMS